Online Banking User Experience: A User Experience Questionnaire (UEQ) Assessment in South Africa - Mujinga, Mathias (Indonesian Journal of Information Systems, 2024)
Online banking has seen tremendous growth driven by the emergence of the fourth industrial (4IR) and innovative technologies in every aspect of our daily activities. Hence, there is an emergence of areas of research around aspects of online banking, such as the need for user experience. This paper evaluates online banking user experience (UX) using the user experience questionnaire (UEQ). The study collected 725 survey responses from UEQ in South Africa, and the findings show a high quality of UX based on a comparison against the UEQ benchmark data set. More specifically, the hedonic quality scale aspect is at the highest level compared to the pragmatic quality aspects of UX. The findings provide practical contributions to online banking designers and developers in retail banks to optimise areas of strength and improve on those aspects that need improvements.